2022
DOI: 10.1080/0886022x.2022.2137421
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella pathogenicity island 1 knockdown confers protection against myocardial fibrosis and inflammation in uremic cardiomyopathy via down-regulation of S100 Calcium Binding Protein A8/A9 transcription

Abstract: Background/Aim Uremic cardiomyopathy (UCM) is a characteristic cardiac pathology that is commonly found in patients with chronic kidney disease. This study dissected the mechanism of SPI1 in myocardial fibrosis and inflammation induced by UCM through S100A8/A9. Methods An UCM rat model was established, followed by qRT-PCR and western blot analyses of SPI1 and S100A8/A9 expression in myocardial tissues. After alterations of SPI1 and S100A8/A9 expression in UCM rats, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…and the expression of inflammatory cytokines (IL-6, TNF-α, and IL-1β) in both the local myocardium and systemic circulation was reduced. 130 These indicate that knockdown of S100A9 can alleviate the inflammatory response and tissue fibrosis in UCM, thereby improving cardiac function. 130 AF is a common arrhythmia caused by various factors such as inflammation and atrial fibrosis.…”
Section: Role Of S100a9 In Cardiomyopathy and Atrial Fibrillationmentioning
confidence: 95%
See 2 more Smart Citations
“…and the expression of inflammatory cytokines (IL-6, TNF-α, and IL-1β) in both the local myocardium and systemic circulation was reduced. 130 These indicate that knockdown of S100A9 can alleviate the inflammatory response and tissue fibrosis in UCM, thereby improving cardiac function. 130 AF is a common arrhythmia caused by various factors such as inflammation and atrial fibrosis.…”
Section: Role Of S100a9 In Cardiomyopathy and Atrial Fibrillationmentioning
confidence: 95%
“…130 These indicate that knockdown of S100A9 can alleviate the inflammatory response and tissue fibrosis in UCM, thereby improving cardiac function. 130 AF is a common arrhythmia caused by various factors such as inflammation and atrial fibrosis. 131 Liu et al 133 identified S100A9…”
Section: Role Of S100a9 In Cardiomyopathy and Atrial Fibrillationmentioning
confidence: 95%
See 1 more Smart Citation
“…192 Potential mechanisms related to myocardial fibrosis in CKD include apoptosis, inflammation, oxidative stress, or renin-angiotensin-aldosterone system activation 193 and may involve FGF23, Klotho, or SPI-1 (salmonella pathogenicity island 1) signaling. 194,195 Metabolic Alterations in the Uremic Heart Structural remodeling in the uremic heart is accompanied by various changes in cardiac metabolism (Figure 2). Recent metabolic studies have revealed disturbances in cardiac energetics and further central processes such as oxidative stress and Ca 2+ handling.…”
Section: Cardiac Metabolism In Uc Structural Remodeling Of the Uremic...mentioning
confidence: 99%
“…192 Potential mechanisms related to myocardial fibrosis in CKD include apoptosis, inflammation, oxidative stress, or renin-angiotensin-aldosterone system activation 193 and may involve FGF23, Klotho, or SPI-1 (salmonella pathogenicity island 1) signaling. 194,195…”
Section: Cardiac Metabolism In Ucmentioning
confidence: 99%